On non-holomorphic functional calculus for commuting operators - Sandberg, Sebastian (MATHEMATICA SCANDINAVICA, 2003)
We provide a general scheme to extend Taylor’s holomorphic functional calculus for several commuting operators to classes of non-holomorphic functions. These classes of functions will depend on the growth of the operator valued forms that define the resolvent cohomology class. The proofs are based on a generalization of the so-called resolvent identity to several commuting operators.